More robust local governance suggests positive effects of long‐term community conservation. Issue 1 (18th November 2020) - Salerno, Jonathan; Andersson, Krister; Bailey, Karen M.; Hilton, Tom; Mwaviko, Kephania K.; Simon, Isaya Donald; Bracebridge, Claire; Mangewa, Lazaro Johana; Nicholas, Aaron; Rutabanzibwa, Harold; Hartter, Joel
Abstract: Community‐based conservation (CBC) is essential to promoting biodiversity protection and livelihood development. Despite significant financial and institutional investment, performance of CBC interventions is mixed, with shortcomings especially evident in wildlife‐based CBC in Africa. CBC outcomes are typically evaluated through household livelihood gains, or through policy analysis at higher administrative levels such as the central state. Surprisingly, village or local governance capacity is often missing from project assessment. Through a controlled study, we evaluate CBC interventions at multiple scales in Tanzania. Employing Bayesian multilevel latent trait models, we find that CBC participation predicts stronger village governance institutions. Additionally, compared to control villages, CBC villages have more local civic organizations and small business enterprise, but do not experience greater elite capture of public goods. Together, and in the absence of direct CBC benefits provisioned to households or signs of success at the higher level of multi‐village CBC bodies, these findings point to the possibility that village‐level governance institutions can adapt in beneficial ways to prolonged CBC interventions.